0D CoP cocatalyst/ 2D g‐C3N4 nanosheets: An efficient photocatalyst for promoting photocatalytic hydrogen evolution. Issue 9 (30th March 2019) - Han, Changcun; Zhang, Tong; Cai, Qijun; Ma, Chonghao; Tong, Zhengfu; Liu, Zhifeng
Abstract: In this work, cobalt phosphide (CoP) nanoparticles were successfully decorated on an ultrathin g‐C3 N4 nanosheet photocatalysts by in situ chemical deposition. The built‐in electric field formed by heterojunction interface of the CoP/g‐C3 N4 composite semiconductor can accelerate the transmission and separation of photogenerated charge‐hole pairs and effectively improve the photocatalytic performance. TEM, HRTEM, XPS, and SPV analysis showed that CoP/g‐C3 N4 formed a stable heterogeneous interface and effectively enhanced photogenerated electron‐hole separation. UV‐vis DRS analysis showed that the composite had enhanced visible light absorption than pure g‐C3 N4 and was a visible light driven photocatalyst. In this process, NaH2 PO2 and CoCl2 are used as the source of P and Co, and typical preparation of CoP can be completed within 3 hours. Under visible light irradiation, the optimal H2 evolution rate of 3.0 mol% CoP/g‐C3 N4 is about 15.1 μmol h −1 . The photocatalytic activity and stability of the CoP/g‐C3 N4 materials were evaluated by photocatalytic decomposition of water. The intrinsic relationship between the microstructure of the composite catalyst and the photocatalytic performance was analyzed to reveal the photocatalytic reaction mechanism.